Clothing and style as nonverbal communication in the society / Asliza Aris, Adlene Aris and Nazirah Mohd. Ba'ai - Aris, Asliza; Aris, Adlene; Mohd. Ba'ai, Nazirah (Universiti Teknologi MARA, 2020)
In fashion, clothing and style is an important tool to evaluate one's significance in the society. Clothing and style have existed from ancient culture up to today's dressing style. The combination of clothing and style create a person's image that allows the wearer to feel comfortable and confident. In the olden days, dress codes were created and were responsible for depicting the social status of the wearer. The variation of clothes style in society became a tradition of symbolic differentiation amongst people in every ethnic all over the world. Today, in fashion, the language of clothes continues its importance as nonverbal communication to portray individuality, self-enhancement, and modernism.